Novel Di Bawah Bayang-Bayang Ode karya Sumiman Udu: Makna Simbolik Penolakan Gelar “Ode” Sebagai Status Sosial Tertinggi Orang Buton: Novel Di Bawah Bayang-Bayang Ode Written by Sumiman Udu: The Meaning of Symbolic Rejection of “Ode” Degree As The Highest Social Status of Buton People - Dara Windiyarti (Balai Bahasa Provinsi Papua, 2020)
The purpose of this study is to describe the symbolic meaning in the novel Di Bawah Bayang-bayang Ode by Sumiman Udu published in 2015. The theory used in this study is symbolic interactional theory. Data collection is done by library techniques. The method used for data analysis is descriptive analysis. This discussion produces the following things. First, the imposition of customs and cultures that are already irrelevant, leading individuals to reject and oppose cultural customs. Second, customary rejection is done by violating norms. Third, customary rejection is done by not doing customary rituals. Fourth, customary rejection is done by removing the title in the name. Fifth, customary rejection is done by pursuing knowledge.